Digital Transformation and Hotel Service Communication: An Analysis of Hilton Garden Inn Jakarta Taman Palem's Readiness - Jaiz, Muhammad; Yuliana, Nina; Yusanto, Yoki; Fitriana, Rina (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation in the hospitality industry is increasingly important for improving the effectiveness of service communications and the quality of the guest experience, especially amidst technology-driven competition. This study aims to analyze Hilton Garden Inn Jakarta Taman Palem's readiness to implement digital transformation through an assessment of organizational aspects, service communications, and digital marketing strategies. The study employed a qualitative approach with data collection techniques including interviews, observations, and documentation studies. Data were analyzed through data reduction, data presentation, and conclusion drawing based on the Miles and Huberman model. The results indicate that the hotel is in the early stages of digitalization, characterized by limited technology utilization for operational functions, service communication quality that does not yet utilize interactive technology, and digital marketing strategies that are still informative and not data-driven. The OnQ system has not been optimally utilized due to variations in human resource digital capabilities, while guest experience support technologies such as self-check-in or automated services are not yet available. This study concludes that successful digital transformation requires improving employee digital literacy, developing more innovative service technologies, and formulating a more targeted digital communication strategy to support the hotel's competitive advantage.